2018
DOI: 10.1038/s41598-018-34738-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CRISPR/Cas9 dosage on TICAM1 and RBL gene mutation rate, embryonic development, hatchability and fry survival in channel catfish

Abstract: The current study was conducted to assess the effects of microinjection of different dosages of guide RNA (gRNA)/Cas9 protein on the mutation rate, embryo survival, embryonic development, hatchability and early fry survival in channel catfish, Ictalurus punctatus. Guide RNAs targeting two of the channel catfish immune-related genes, toll/interleukin 1 receptor domain-containing adapter molecule (TICAM 1) and rhamnose binding lectin (RBL) genes, were designed and prepared. Three dosages of gRNA/Cas9 protein (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Thus, tissue patterns of expression may or may not be the same when the F 1 generation is produced. However, when our laboratory used CRISPR/Cas9 to produce knockouts without accompanying gene insertion, mosaicism was low and similar among all tissues evaluated 9 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, tissue patterns of expression may or may not be the same when the F 1 generation is produced. However, when our laboratory used CRISPR/Cas9 to produce knockouts without accompanying gene insertion, mosaicism was low and similar among all tissues evaluated 9 .…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have successfully obtained large genomic deletion using dual guide RNAs (gRNAs) in mammalian cells and animal models such as mouse and zebrafish 17,18 . Deletion mutations of up to 900 bp were recently achieved in channel catfish targeting the toll/interleukin 1 receptor domain-containing adapter molecule (TICAM 1) using a single guide RNA 9 . Moreover, Li et al 8 reported that the CRISPR/Cas9 system could effectively generate desirable non-coding sequence mutants in Nile tilapia (Oreochromis niloticus).…”
mentioning
confidence: 99%
“…The mutation frequency of the embryos increased with greater dosages of gRNA/Cas9 [194]. Higher dosages of gRNA/Cas9 also resulted in decreased hatching percentage and increased mortality [194]. More research is needed to elucidate the relationship between CRISPR-Cas9 dosage and off-target effects.…”
Section: Knowledge Gapmentioning
confidence: 99%
“…The dosage of Cas9 has been demonstrated to alter both its specificity and kinetics, with a 2-fold drop in on-target efficiency alongside a 7-fold increase in the specificity ratio when the Cas9 dosage is decreased by 5-fold during plasmid transfection [ 193 ]. Additional study investigated the possibility of a dose-dependent effect of the gRNA with the Cas9 protein on channel catfish ( Ictalurus punctatus) mutation rate and embryonic survival [ 194 ]. The mutation frequency of the embryos increased with greater dosages of gRNA/Cas9 [ 194 ].…”
Section: Knowledge Gapmentioning
confidence: 99%
See 1 more Smart Citation